Analisis Perbedaan Tipe Somatotype dan Aspek Fisiologis terhadap Kecepatan Lari 100 Meter - Husni Mubarroq; Arya T Candra; Moh. Agung Setiabudi (MAN Insan Cendekia Jambi, 2026)
This study aimed to analyze the differences in somatotype and physiological aspects regarding 100-meter sprint speed. A quantitative descriptive method was employed. The sample consisted of 20 athletes from the Puputan Bayu Athletics Club, selected using purposive sampling. Data collection involved testing and measurements, specifically assessing body type, leg muscle strength, leg muscle explosive power, leg muscle flexibility, and 100-meter sprint speed. The results indicated that neither the somatotypes nor the physiological aspects examined had a significant influence on 100-meter sprint speed. For the endomorph somatotype, the F-test significance value was 0.621, while the significance values ​​for leg strength, explosive power, and flexibility were 0.563, 0.968, and 0.380, respectively; all these values ​​exceeded 0.05. For the mesomorph somatotype, the F-test significance value was 0.375, with individual variable values ​​of 0.198 for leg muscle strength, 0.355 for leg muscle explosive power, and 0.303 for leg muscle flexibility—all above 0.05. For the ectomorph somatotype, the F-test significance value was 0.387, with values ​​of 0.220 for leg muscle strength, 0.386 for leg muscle explosive power, and 0.995 for leg muscle flexibility, all of which were greater than 0.05.